2021
DOI: 10.1016/j.soard.2021.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative chronic opioid use and its impact on early complications in bariatric surgery: a Swedish nationwide cohort study of 56,183 patients

Abstract: Please cite this article as: RRH: Impact of opioids in bariatric surgery This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…Our estimate on the prevalence of long‐term opioid use was higher than in previous Nordic studies that have required longer use periods 9,10,14 . Most other studies have also had specific populations, very commonly post‐operative patients 11–13,15,16,18 . Similarly to the current study, Quinn et al 21 studied long‐term opioid use among all incident users in Sweden with requirements similar to ours, that is, at two dispensations within 6 months, estimating its prevalence to 7.6% 21 .…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Our estimate on the prevalence of long‐term opioid use was higher than in previous Nordic studies that have required longer use periods 9,10,14 . Most other studies have also had specific populations, very commonly post‐operative patients 11–13,15,16,18 . Similarly to the current study, Quinn et al 21 studied long‐term opioid use among all incident users in Sweden with requirements similar to ours, that is, at two dispensations within 6 months, estimating its prevalence to 7.6% 21 .…”
Section: Discussionsupporting
confidence: 71%
“…9,10,14 Most other studies have also had specific populations, very commonly post-operative patients. [11][12][13]15,16,18 Similarly to the current study, Quinn et al 21 studied long-term opioid use among all incident users in Sweden with requirements similar to ours, that is, at two dispensations within 6 months, estimating its prevalence to 7.6%. 21 However, they did not include the so-called weak opioids into their analyses and did not require a minimum amount of opioids to be dispensed.…”
Section: Discussionmentioning
confidence: 52%
“…[9][10][11] Most other studies have also had speci c populations, very commonly post-operative patients. 12,13,15,[19][20][21] Similarly to the current study, Quinn et al (2019) studied long-term opioid use among all incident users in Sweden with requirements similar to ours, i.e., at two dispensations within six months, estimating its prevalence to 7.6%. 36 However, they did not include the so-called weak opioids into their analyses and did not require a minimum amount of opioids to be dispensed.…”
Section: Discussionsupporting
confidence: 52%
“…Similarly to global research, multiple studies have assessed long-term opioid use in the Nordic countries. 9,10,[19][20][21][11][12][13][14][15][16][17][18] All Nordic countries offer similar potential to study opioid use from comprehensive, nationwide registers of prescription drug dispensations, or so-called prescription registers. 22 However, previously conducted studies have de ned their exposure very dissimilarly, with up to years of opioid use being required to qualify for "long-term use".…”
Section: Introductionmentioning
confidence: 99%
“…Altogether, this makes different types of pain-related pharmacologic treatments common among bariatric patients. We have recently reported that preoperative opioid use is a risk factor for severe complications after bariatric surgery [11] and Raebel et al [12] found an increased use of opioids after bariatric surgery. Treatment of chronic pain with opioids is controversial because of addiction as well as a significant number of side effects [13].…”
mentioning
confidence: 93%